Energy expenditure estimation during activities of daily living in middle-aged and older adults using an accelerometer integrated into a hearing aid - Stutz, Jan; Eichenberger, Philipp A.; Stumpf, Nina; Knobel, Samuel E. J.; Herbert, Nicholas C.; Hirzel, Isabel; Huber, Sacha; Oetiker, Chiara; Urry, Emily; Lambercy, Olivier; Spengler, Christina M. (Frontiers in Digital Health, 2024)
BackgroundAccelerometers were traditionally worn on the hip to estimate energy expenditure (EE) during physical activity but are increasingly replaced by products worn on the wrist to enhance wear compliance, despite potential compromises in EE estimation accuracy. In the older population, where the prevalence of hearing loss is higher, a new, integrated option may arise. Thus, this study aimed to investigate the accuracy and precision of EE estimates using an accelerometer integrated into a hearing aid and compare its performance with sensors simultaneously worn on the wrist and hip.MethodsSixty middle-aged to older adults (average age 64.0 ± 8.0 years, 48% female) participated. They performed a 20-min resting energy expenditure measurement (after overnight fast) followed by a standardized breakfast and 13 different activities of daily living, 12 of them were individually selected from a set of 35 activities, ranging from sedentary and low intensity to more dynamic and physically demanding activities. Using indirect calorimetry as a reference for the metabolic equivalent of task (MET), we compared the EE estimations made using a hearing aid integrated device (Audéo) against those of a research device worn on the hip (ZurichMove) and consumer devices positioned on the wrist (Garmin and Fitbit). Class-estimated and class-known models were used to evaluate the accuracy and precision of EE estimates via Bland-Altman analyses.ResultsThe findings reveal a mean bias and 95% limit of agreement for Audéo (class-estimated model) of −0.23 ± 3.33 METs, indicating a slight advantage over wrist-worn consumer devices (Garmin: −0.64 ± 3.53 METs and Fitbit: −0.67 ± 3.40 METs). Class-know models reveal a comparable performance between Audéo (−0.21 ± 2.51 METs) and ZurichMove (−0.13 ± 2.49 METs). Sub-analyses show substantial variability in accuracy for different activities and good accuracy when activities are averaged over a typical day's usage of 10 h (+61 ± 302 kcal).DiscussionThis study shows the potential of hearing aid-integrated accelerometers in accurately estimating EE across a wide range of activities in the target demographic, while also highlighting the necessity for ongoing optimization efforts considering precision limitations observed across both consumer and research devices.